Reclaiming the universal postcolonial readings of selected anglophone poems by Filipino poets - Garcia, J. Neil C. (2014)
After giving a summary of postcolonial theory’s understanding of universalism, the author of this article critically “re-functions” and re-contextualizes this concept within the history of postcolonial literatures, defining it as a textual “register” rather than just a theme. In this manner, he pursues the argument that the universalist trope can indeed be “postcolonially reclaimed”—a task that is carried out in his readings of a selection of well-known lyric texts written by some of the most important poets of the Philippines’ anglophone tradition. Crucial to this project is the recognition of the multiplicity of postcolonial modes of writing, most of which do not self-consciously traffic in the particularities of ethnopoetic “local-coloring.” Instead, they interpretively require—despite their seemingly self-evident accessibility and assimilability— a ruthlessly specifying, critical approach. This is an approach that seeks, first and foremost, to locate a text resolutely within the context of its production and intended consumption. Germane to this activity is the idea that the universal, once situated, is always specific. Suffice it to say that Philippine literature’s many (mostly lyric) gestures toward “generality” and “abstraction” need to be seen in this historicizing light.
Keywords: Postcolonialism; Filipino poets